ANALISA NILAI KEKASARAN PERMUKAAN MAGNESIUM YANG DIFREIS DALAM KONDISI TERSUPLAI UDARA DINGIN - Gusri Akhyar Ibrahim (JURNAL KAJIAN TEKNIK MESIN, 2016)
The use of magnesium material, as alternative to iron and steel, is becoming more popular. Besides the fact that it is lighter, magnesium is popular because it is available in a quite large quantity in this world. To make magnesium to be a machine component, there is a process needed to be done, which is known as machining process. The machining process done in several conditions doe to the pharamater or factor in machining process.. The examples of cutting pharameter are feed rate, cutting speed, and deep of cutting. This research used magnesium as the material of research. The purpose of this research is to investigate the influence of cutting pharameter to the surface roughness of magnesium machined with milling process ang supplied with cooling air from vortex tube cooler. Cutting pharameter used in this research are feed rate and cutting speed. Feed rate used was three levels, those are 0,15 mm/rev, 0,20 mm/rev, and 0,25 mm/rev. Cutting speed used also three levels, those are 23,18 m/min, 32,15 m/min and 42,7 m/min. Cooling air is released from vortex tube cooler with 15 oC of temperature. The result of this research is found that feed rate affect the number of magnesium surface roughness very significan. It can makes the number of surface roughness higher. Another pharameter, cutting speed also affect the number of magnesium surface roughness. It can make the number of surface roughness decreased. The number of magnesium surface roughness is also affected by nose radius, vibration, and cutting force.Keywords: magnesium material, surface roughness, milling, cutting pharameter, cooling air.